2020
DOI: 10.1177/2048872619872847
|View full text |Cite
|
Sign up to set email alerts
|

Current status of the management and outcomes of acute aortic dissection in Japan: Analyses of nationwide Japanese Registry of All Cardiac and Vascular Diseases-Diagnostic Procedure Combination data

Abstract: Background: Despite recent advances in the diagnosis and management, the mortality of acute aortic dissection remains high. This study aims to clarify the current status of the management and outcome of acute aortic dissection in Japan. Methods: A total of 18,348 patients with acute aortic dissection (type A: 10,131, type B: 8217) in the Japanese Registry of All Cardiac and Vascular Diseases database between April 2012–March 2015 were studied. Characteristics, clinical presentation, management, and in-hospital… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 35 publications
(14 citation statements)
references
References 40 publications
0
10
0
Order By: Relevance
“…In a recent study based on the nationwide Japanese Registry of All Cardiac and Vascular Disease database, Yamaguchi and colleagues demonstrated that the median hospital stay among patients who survived was 28 days in type A AD and 22 days in type B AD due to rehabilitation and nursing care during the same hospitalization period. 23 24 …”
Section: Discussionmentioning
confidence: 99%
“…In a recent study based on the nationwide Japanese Registry of All Cardiac and Vascular Disease database, Yamaguchi and colleagues demonstrated that the median hospital stay among patients who survived was 28 days in type A AD and 22 days in type B AD due to rehabilitation and nursing care during the same hospitalization period. 23 24 …”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, the Japanese Registry of All Cardiac and Vascular Diseases database has the data of patients who had medical or surgical treatment for acute type A aortic dissection. 10 Patients who had non-surgical treatment comprised 33% of 10,131 patients from April 2012 to March 2015. The early mortality of patients with medical treatment was reported to be much higher (49.7%) compared to surgical cases (11.8%).…”
Section: Current Status Of Treatment For Acute Aortic Dissection In Databases and Registriesmentioning
confidence: 99%
“…The epidemiology of acute aortic syndromes is further elucidated in a descriptive analysis of 18,348 patients with acute aortic syndrome captured in the Japanese Registry of All Cardiac and Vascular Diseases. 3 This large dataset provides novel insight into possible seasonal variations in the incidence of acute aortic syndromes (autumn–winter predominant), and important trends in approaches to management, with a more than two-fold increase in the use of endovascular management of type B dissection. Unfortunately, although outcomes are improving, mortality rates remain high, particularly for type A dissection (24.3%) and most notably for those not treated surgically (49.7%); again underscoring the need for better prevention and early diagnosis and treatment.…”
Section: Epidemiologymentioning
confidence: 99%